Retraction: Effect of short-term thiamine supplementation on oxidative stress, inflammation, exercise capacity and prognosis in chronic heart failure: a randomized clinical trial: Retraction: Thiamine in the treatment of CHF. - Geng, Like; He, Sanjun; Wang, Luzhao; Dang, Qun; Wang, Fang; Lv, Guo (Progress in Nutrition, 2023)
THIS ARTICLE HAS BEEN RETRACTEDBackground and aim: Thiamine has known antioxidative and anti-inflammatory effects. However, the effectiveness of thiamine supplementation and clinical outcome in chronic heart failure (CHF) are unclear. Therefore, this study focuses on evaluating the effect of short-term thiamine supplementation on oxidative stress, inflammation, exercise capacity, and predicts the ability of rehospitalization within 30-day in patients with CHF.Methods: Sixty hospitalized patients with CHF were randomly divided into two groups. Both groups received conventional anti-heart failure treatment, but the thiamine group (n=30) received thiamine (100 mg/day) by intramuscular injection for 1 week, while the control group (n=30) did not do it. Serum thiamine, malondialdehyde (MDA), superoxide dismutase (SOD), high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), pro-B-type natriuretic peptide (pro-BNP) levels and 6-minute walking distance (6MWD) were detected in the two groups before and after the treatment, and all the participants were followed-up for 30-day after discharge.Results: After 1 week of treatment, serum thiamine levels were significantly decreased in control group compared with baseline (p＜0.05), and the SOD levels and 6MWD in the thiamine group were significantly increased compared with the control group (p＜0.05). Serum thiamine levels in the thiamine group were independent determinants of serum SOD levels (standardized coefficient=0.4, p=0.022) and 6MWD (standardized coefficient=0.518, p=0.004) after thiamine supplementation. Serum thiamine levels before discharge (hazard ratio [HR], 0.957, 95% confidence interval [CI], 0.924 to 0.992; p=0.016) was independently related to the rehospitalization within 30-day.Conclusions: In conclusion, short-term thiamine supplementation could improve oxidative stress and exercise capacity, and serum thiamine levels before discharge was an independent predictor of rehospitalization within 30-day. Meanwhile, furosemide could reduce serum thiamine levels in patients with CHF.